Efficacy of Virechana Karma along with Shamana Ausadha in Vipadika w.s.r to Palmar Psoriasis (International Journal of Ayurveda and Pharma Research, 2024)
Healthy skin depicts a healthy life. The skin is the largest organ and also a protecive covering for more delicate and funcionally sophisticated internal vicera. The skin was appreciated primarily as a passive barrier to fluid loss and mechanical injury. Many interrelated factors affects both the appearence and health of the skin including nutrition, hygiene, circulation, age, immunity, genetic traits, psychological state and drugs. Skin conditions can affect anyone- young and old, men and women. Acne vulgaries, psoriasis, eczema, urticaria etc are just a few examples of common skin disorders. Treating skin diseases is like, fighting war and if the warriors want to win, it is necessary to accurately access the strength of the adversary. So accurate diagnosis, application of principle, understanding the Avastha, treatment based on Avastha are highly essential. Vipadika is one of the types of the Kshudrakushta in Ayurveda. Here a 57 years old male patient history of repeted exposure to a chemical substance in paddy field with complain of excessive dryness, pain and fissures in palms since 1 year, diagnosed as Vipadika (palmer psoriasis) was treated with Sodhana (Virechana karma with Tivrit Avaleha) as well as Samana ausadhi with Trikatu churna, Mahatikta Ghrita, Khadiraarista, Panchatikta Ghrita guggul and Nimba taila (local application) having marked improvement. The study showed that combination of Ayurvedic modalities gives significant result in Lakshanas (symptoms) like Panisphutana (fissures in palms), Tivravedana (severe local pain), Daha (burning sensation), Kandu (itching) in a span of about 1 month.